Effect of feeding management practices on performance of calf - SINGH, GHANSHAM; SAINI, A L; TIWANA, M S (The Indian Journal of Animal Sciences, 2013)
Newly born Murrah buffalo calves (24) up to 6 months of age were observed to study the effect of milk feeding systems (pail vs suckling) and supplementation of milk with feed addidves (biovet and flavomycin) on the growth performance. The live weight of calves increased form birth to 6 months of age by 54.86, 64.56, 72.46, and 70.26 kg in pail fed, suckled, biovet supplemented and flavomycin-supplemented groups respectively. Growth rate was significantly higher in supplemented groups than control group. Body length, height and heart girth also reflected beneficial effect of feed additives. All the calves survived without showing any marked sign of morbidity. Additional cost of feed supplemented was compensated by increased growth rate, higher resistance against diseases and it is expected to improve reproductive performance and life-time productivity at the later stages.